ANALISIS PENENTUAN HARGA POKOK PRODUKSI WOODCRAFT FURNITURE BERDASARKAN JOB ORDER COSTING - Novita, Dewi B1031151030 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
The purpose of this study is to determine whether the collection of cost of goods manufactured based on orders (job order costing) has been implemented by Mr. Maman's Woodcraft Furniture business in accordance with qualitative standards, while data collection is done by listing questions and direct interviews with their owners about the company's activities and determination the cost of production in the business.This research was carried out in Mr. Maman's Woodcraft Furniture business which is a business engaged in manufacturing whose main activity is to make furniture specifically for Makeup Artists such as beauty cases and vanity mirrors that use plywood-based materials. This business carries out production activities based on orders and there is no product inventory in the workshop. After conducting the research, the conclusion drawn from this research is that the business of Woodcraft Furniture owned by Mr. Maman has not used the cost of order method correctly in accordance with the applicable accounting standards. in the expense report.Ahmad & Wasilah. (2009). Akuntansi Biaya. Salemba Empat: Jakarta.Armanto Witjaksono. (2013). Akuntansi Biaya. Graha Ilmu: Yogyakarta. Ahmad, Firdaus dan Wasilah Abdullah, (2012). Akuntansi Biaya Edisi 3. Salemba Empat: Jakarta.Anis Wuryansari, (2016) Skripsi: Analaisis Perhitungan Harga Pokok Produksi Dengan Menggunakan Metode Full Costing Sebagai Dasar Penentuan Harga Jual (Studi Kasus di Perternakan Seraphine Yogyakarta).Batubara, Helmina (2013). Penentuan Harga Pokok Produksi Berdasarkan Metode Full Costing pada Pembuatan Etalase Kaca dan Alumunium di UD. Istana Alumunium Manado. Jurnal EMBA Vol. 1 No. 3:217-224 ISSN 2303-1174.Bustami, B., & Nurela. 2010. Akuntansi Biaya Edisi 2. Mitra Wacana Media. Jakarta.Daljono. (2011). Akuntansi Biaya Penentuan Harga Pokok dan Pengendalian. Edisi ketiga, Badan  Penerbit Universitas Diponegoro, Semarang.Hansen, Don R. Maryanne M Mowen. 2012 Management Accounting 7th.Diterjemahkan oleh Tim Penerjemah Penerbit Salemba. Akuntansi Manajemen, Edisi 8. Buku 1. Salemba Empat: Jakarta.Hasan, Iqbal. (2002). Pokok-Pokok Materi Metodologi dan Aplikasinya. Ghalia Indonesia: Jakarta.Krismiaji, Aryani Y. Anni, (2011). Akuntansi Manajemen. Edisi Kedua. Cetakan Pertama. UPP STIM YKPN. Yogyakarta.Mulyadi, (2010). Akuntansi Biaya. Penerbit UPP STIM YKPN: Yogyakarta.Mulyadi,  (2012). Akuntansi Biaya. Penerbit UPP STIM YKPN: Yogyakarta.Mulyadi, (2015). Akuntansi Biaya Edisi 5. Penerbit UPP STIM YKPN: Yogyakarta.Moleong, Lexy J. (2007) Metodologi Penelitian Kualitatif. Penerbit PT Remaja Rosadakarya Offset: Bandung.